Is the long-term mortality similar in COVID-19 and community-acquired pneumonia? - Méndez, Raúl; González-Jiménez, Paula; Latorre, Ana; Mengot, Noé; Zalacain, Rafael; Ruiz, Luis A.; Serrano, Leyre; España, Pedro P.; Uranga, Ane; Cillóniz, Catia; Hervás, David; Torres, Antoni; et al. (Frontiers in Medicine, 2023)
Introduction: There are no data on the impact conferred association of type of pneumonia and long-term mortality by the type of pneumonia (COVID-19 or communityacquired pneumonia [CAP]) on long-term mortality after an adjustment for potential confounding variables. We aimed to assess the type of pneumonia and risk factors for long-term mortality in patients who were hospitalised in conventional ward and later discharged.Methods: Retrospective analysis of two prospective and multicentre cohorts of hospitalised patients with COVID-19 and CAP. The main outcome under study was 1year mortality in hospitalised patients in conventional ward and later discharged. We adjusted a Bayesian logistic regression model to assess associations between the type of pneumonia and 1-year mortality controlling for confounders.The study included a total of 1693 and 2374 discharged patients in the COVID-19 and CAP cohorts, respectively. Of these, 1525 (90.1%) and 2249 (95%) patients underwent analysis. Until 1-year follow-up, 69 (4.5%) and 148 (6.6%) patients from the COVID-19 and CAP cohorts, respectively, died (p=0.008). However, the Bayesian model showed a low probability of effect (PE) of finding relevant differences in long-term mortality between CAP and COVID-19 (odds ratio 1.127, 95% credibility interval 0.862-1.591; PE = 0.774) Conclusions: COVID-19 and CAP have similar long-term mortality after adjusting for potential confounders.